Sensitivity and missed cancer rate in the symptomatic breast clinic—A retrospective cohort study of 40 323 patients. Issue 3 (26th December 2020) - Batt, Jeremy; Ainsworth, Rachel; Rayter, Zenon; Nickells, James; Valencia, Alexandra
Abstract: Introduction: Symptomatic presentations account for the majority of invasive breast cancer diagnoses. While the National Health Service Breast Screening Programme is subjected to strict quality control, no such system for performance monitoring exists in the symptomatic clinic. We assess the sensitivity of cancer detection and missed cancer rate for symptomatic breast patients to benchmark future outcome measures. Methods: A retrospective cohort study of patients attending the symptomatic breast clinic between October 2013 and October 2018 was performed. Patients with new cancer diagnoses were identified and screened for those who had presented to the department within the 3 years prior to their diagnosis. From this, the sensitivity and missed cancer rate were calculated. Results: About 40 323 patients were seen over the 5‐year study period. About 2155 new cancers were diagnosed, with 2033 identified at their initial clinic attendance. A further 122 patients had cancer diagnosed on a subsequent appointment, of which 23 patients were considered to have had a delay in diagnosis. The sensitivity of the one‐stop symptomatic breast clinic was therefore 99.0%, and the missed cancer rate was 0.06% over 5 years. Conclusion: The missed cancer rate reported in this study is favorable compared to the outcomes reported in the National Health Service Breast Screening Programme and superior to the only other study reporting outcomes on a much smaller cohort. The unit in question therefore is performing exceptionally against current standards and sets a benchmark against which future performance can be measured.